Conversations about Philosophy. - Burton, Howard (Open Agenda Publishing, 2021)
Conversations About Philosophy, Volume 2, is a five-part Ideas Roadshow Collection of carefully-edited Ideas Roadshow Conversations featuring leading researchers with a detailed preface highlighting the connections between the different books. All five books include a detailed essay setting up the different ideas and questions for discussion at the end of each chapter. The following experts have participated in this Collection: 1. Brian Epstein, Associate Professor of Philosophy at Tufts University;2. Onora O'Neill, Emeritus Professor of Philosophy at the University of Cambridge and a crossben.
Description based upon print version of record.
Keywords: Kant, Immanuel, -- 1724-1804.; Spinoza, Benedictus de, -- 1632-1677.; Kant, Immanuel, -- 1724-1804; Spinoza, Benedictus de, -- 1632-1677; Philosophy.; Meaning (Philosophy); Philosophy; Philosophie.; Signification (Philosophie); philosophy.; Renaissance.; HISTORY.; Ancient & Classical.; History & Surveys.; PHILOSOPHY.